2013
DOI: 10.7705/biomedica.v34i0.2122
|View full text |Cite
|
Sign up to set email alerts
|

Sensibilidad antimicrobiana in vitro en aislamientos de Enterococcus faecalis y Enterococcus faecium obtenidos de pacientes hospitalizados

Abstract: Contribución de los autores:Manuel Medell: caracterización de cepas y redacción del documento. Marcia Hart y María Luisa Batista: recolección de cepas y revisión del manuscrito. ARTÍCULO ORIGINAL Biomédica 2014;34(Supl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…El género Enterococcus está conformado por 36 especies de bacterias grampositivas de morfología cocoide, anaerobias facultativas y catalasa negativas; las que se relacionan más frecuentemente con procesos infecciosos son E. faecalis y E. faecium (1). Anteriormente se consideraba a estas bacterias como poco virulentas.…”
Section: Introductionunclassified
“…El género Enterococcus está conformado por 36 especies de bacterias grampositivas de morfología cocoide, anaerobias facultativas y catalasa negativas; las que se relacionan más frecuentemente con procesos infecciosos son E. faecalis y E. faecium (1). Anteriormente se consideraba a estas bacterias como poco virulentas.…”
Section: Introductionunclassified
“…It is interesting to note that as previous studies showed the rate of resistance in Zanjan hospitals is notably low in comparison to hospitals of other cities of Iran such as Uromiyeh, Tabriz, Tehran or other countries such as Cuba and Pakistan. [29][30][31][32][33] Our investigations hypothesized that there are some main reasons regard to this occurrence. Firstly, majority of disinfectants which are prepared and used in hospitals of Zanjan are strong and fast acting ones.…”
Section: Disinfectantmentioning
confidence: 99%